“Diving” cyclones and consequences of their impact on the coasts of the South-Eastern Baltic Sea - Stont Zhanna Ivanovna; Bobykina V. P.; Ulyanova Marina (Russian Journal of Earth Sciences, 2023)
A generalization of historical data for more than 40 years on destructive cyclones observed on the coast of the South-East Baltic Sea has been made. According to the trajectories reconstructed using the HYSPLIT calculation model, cyclones with a northern trajectory, the so-called “diving” cyclones, were identified. A register of such cyclones has been compiled, showing their increasing occurrence: since the 80s of the last century, two such cyclones have passed (1981 and 1983), and since the beginning of thiscentury, over a 22-year period – 14. They differ in a significant acceleration length – about 1000 km from the Gulf of Bothnia to the southeastern coast of the Baltic Sea and have high potential energy. At the same time, atmospheric vortices cause wind waves up to 7–8 meters high. They are associated with significant, sometimes catastrophic, abrasion and retreat of coasts, especially the northern exposure, as well as the destruction of the coastal infrastructure of resort towns, including federal ones, historically concentrated on the northern coast of the Kaliningrad (Sambia) Peninsula of the Kaliningrad Region. The degree of destruction after the impact of each cyclone depends on the prehistory of its formation and development, the height of the surge of coastal waters, and the morphological features of the coast. There are two main scenarios for the development of seasonal storm activity. For example, in the winter season 2011–2012 and 2018–2019 after active cyclones with strong westerly winds of more than 20 m/s, which raised the sea level to +(40–60) cm, the approach of a “diving” cyclone with storm northerly winds caused an instant “splash” of the level up to +(100–120) cm above the ordinary (the marked maximum was 160 cm), which corresponds in order of magnitude to the heights of the beach. The second scenario is associated with the development of a series (cluster) of cyclones. It manifested itself especially clearly in the winter season of 2022, when four “diving” cyclones passed with short windows of good weather. The western cyclone was the final one. On the coast of the Kaliningrad Region, the level rose significantly. Both scenarios of the passage of “diving” cyclones are associated with the greatest storm damage to the coast of the Kaliningrad Region.